2021
DOI: 10.4236/ojped.2021.111004
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Experience of Children and Adolescents with Homozygous Sickle Cell Disease in Brazzaville

Abstract: Introduction: Sickle cell disease, the most frequent hemoglobinopathy, is one of many causes of psychological repercussions. Objectives: To determine the prevalence of psychological disorders in children/adolescents living with sickle cell disease and to identify the associated factors. Patients and Method: An analytical cross-sectional study was conducted from June to September 2019 at the national sickle cell center and at the mother-child consultation of the University Hospital of Brazzaville. Children/adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Not only that, fatigue and weakness that appear as effects of anemia can harm teenagers in their daily activities, reducing their energy levels and productivity. 21 .Lastly, anemia can also contribute to impaired mood and emotional well-being in adolescents, resulting in mood swings and lowered overall levels of psychological well-being 17,22 Therefore, an indepth understanding of the impact of anemia on adolescents is essential in efforts to maintain the health and well-being of this young generation.…”
Section: Discussionmentioning
confidence: 99%
“…Not only that, fatigue and weakness that appear as effects of anemia can harm teenagers in their daily activities, reducing their energy levels and productivity. 21 .Lastly, anemia can also contribute to impaired mood and emotional well-being in adolescents, resulting in mood swings and lowered overall levels of psychological well-being 17,22 Therefore, an indepth understanding of the impact of anemia on adolescents is essential in efforts to maintain the health and well-being of this young generation.…”
Section: Discussionmentioning
confidence: 99%
“…Kshaish & Aziz, (2020), carried out a descriptive study about assessment of daily living activities for (100) thalassemic school age children in Baghdad city, they also find most of children are affected moderately in all domains of daily living activities [27] . A crosssectional study directed by (Moyen et al, 2021), on 201 patients with SCD aged (6_19 years old) in order to determine the (Psychological Experience for Children with Homozygous SCD in Brazzaville) which found that the impact of disease on the patient's daily life was negative in all cases [28] .…”
Section: Discussionmentioning
confidence: 99%
“…In a study from Brazzaville, it was found that in children/adolescent group 76.1% had disempowerment, 29.9% had anxiety and 5.5% had depression. Study suggested that stronger focus on education, behavior modification, and communication is necessary to improve the quality of care due to the prevalence of psychiatric illnesses in children and adolescents who live with SCD 9 . A previous study from India found that children with SCD have more psychological issues than children without SCD.…”
Section: Psychological Problems Of Scdmentioning
confidence: 99%